Estudos visando a síntese e avaliação farmacológica de novos protótipos à fármacos inibidores de acetilcolinesterase planejados a partir do Donepezil - Simões, Maria Cecília Rodrigues (2013)
Alzheimer disease (AD) is a neurodegenerative disease clinically characterized by a progressive memory loss, which results in psychical and motor disfunction (FARRAN, JAMES, et al., 2011). Due to the large worldwide number of people with this disease, it is a challenge to science and public health. Therefore, projects aiming the disease symptomatic treatment and a patient progressive improvement are essential. Previous studies at the Laboratory of Phytochemistry and Medicinal Chemistry - LFQM -in Federal University of Alfenas - UNIFAL-MG, led to the discovery of the substance LFQM-18 (6 Figure 9) (new substance that presented a preliminary activity of acetylcholinesterase inhibitory), which was a prototype on the genesis of new compounds capable of acting as therapeutic agents in neurodegenerative diseases, especially Alzheimer's disease (AD). An analogous series of LFQM-18 was proposed and 10 new intermediary substances were synthesized and studied, validating the synthetic route for obtaining them. It was obtained, as a final product, acylhydrazone 17, evaluated preliminarily through Marston's test, which has indicated a low activity for the compound. Additional studies are ongoing to confirm the AChE inhibitory activity for compound 17.